2015
DOI: 10.1007/s00344-015-9521-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-Mediated Tolerance and Resistance to Plants Under Abiotic and Biotic Stresses

Abstract: Plant growth-promoting bacteria (PGPB) are capable of alleviating environmental stress and eliciting tolerance in plants to promote their growth. Several PGPB elicit physical and/or chemical changes related to plant defense in the form of induced systemic resistance (ISR) under biotic stress. Researchers emphasized that PGPBelicited ISR has suppressed plant diseases caused by a range of pathogens in both the greenhouse and field. PGPB-elicited physical and chemical changes in plants result in enhanced toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(68 citation statements)
references
References 221 publications
(75 reference statements)
3
63
1
1
Order By: Relevance
“…There are increasing reports indicating that PGP bacteria can diminish the stress of plants when grown on sediments with different physicochemical properties and/or with high metal pollution levels (Yang et al, 2008;Rajkumar et al, 2012;Mateos-Naranjo et al, 2015a, 2015bUllah et al, 2015;Choudhary et al, 2016) although not so much information is available on the effect at the stage of seed germination (Miransari and Smith, 2014). Thus, it has been reported that the phase of germination is more sensitive to environmental factors and/or metal contamination than other phases of plants life cycle by the absence of some defense mechanisms to cope with these stressful conditions (Liu et al, 2005;Xiong and Wang, 2005;Mateos-Naranjo et al, 2008c).…”
Section: Resultsmentioning
confidence: 99%
“…There are increasing reports indicating that PGP bacteria can diminish the stress of plants when grown on sediments with different physicochemical properties and/or with high metal pollution levels (Yang et al, 2008;Rajkumar et al, 2012;Mateos-Naranjo et al, 2015a, 2015bUllah et al, 2015;Choudhary et al, 2016) although not so much information is available on the effect at the stage of seed germination (Miransari and Smith, 2014). Thus, it has been reported that the phase of germination is more sensitive to environmental factors and/or metal contamination than other phases of plants life cycle by the absence of some defense mechanisms to cope with these stressful conditions (Liu et al, 2005;Xiong and Wang, 2005;Mateos-Naranjo et al, 2008c).…”
Section: Resultsmentioning
confidence: 99%
“…Notable reports among those are Azospirillum strains helping to cope with salt stress [126][127][128] and Bacillus and Azospirillum leading to improve heat tolerance in wheat [129].…”
Section: Alleviation Of Abiotic Stress In Wheat By Pgprmentioning
confidence: 99%
“…N 2 -fixing bacteria fulfill the nitrogen requirement of several plants in nitrogen-depleted soils [3]. Plant growth-promoting rhizobacteria (PGPR) stimulate plant growth by synthesizing phytohormones and vitamins and exert protective effects on plants against both abiotic and biotic stresses through a variety of well-documented mechanisms [4]. PGPR counteract the water stress by producing exopolysaccharides that alter the soil texture and allow more effective root penetration in the soil.…”
Section: Introductionmentioning
confidence: 99%